The role of social media in shaping health behaviors of the general population during the COVID-19 pandemic - Dimitrinka Jordanova Pesevska; Ana Tomovska Misoska; Ljupco Efremov; Kate Trajkova; Tamara Mitanovska; Ivan Dodovski (University American College Skopje, 2021)
Information from social media can have a strong influence on health behaviors in general population. The aim of this study is to explore the association between exposure to COVID-19 information gained through social media and health behaviors in line with public health recommendations, including COVID-19 vaccine intention and immunization. The study is based on a survey conducted online between 15 May and 30 June 2020 using a snowball sampling strategy. A total of 353 participants from the Republic of North Macedonia (67% female and 33% male) were included in the study. The measurements were developed by the University of Konstanz, as a part of a multi-county study design which comprised of a several scales including social media scale (e.g. Facebook, Twitter, Instagram) and health behaviors scale (including COVID-19 vaccine intention). The results suggest that there is a statistically significant correlation between information gathered from social media and particular health behaviors (e.g. purchase of disinfectant; avoidance of shaking hands; and face touching). Additionally, statistically significant correlation is found between information on social media and the intention for vaccination in case of no complications. The findings highlight the important role that social media play in periods of pandemic. Furthermore, the results clearly support the conclusion that dissemination of information through social media during a pandemic can be essential for shaping the health behaviors of the general population.
Keywords: 330; COVID-19; social media; health behaviors; vaccination